Characterization of the sludge produced in textile laundries in Agreste region of Pernambuco for use in alternative construction materials (Research, Society and Development, 2021)
The textile sludge is a waste resulting of the physicochemical treatment procedure carried out in the effluent of textile laundries. This material is classified by the Brazilian standard as a non-hazardous waste considering that, despite its varied chemical composition, its components do not present great risks of human contamination. In view of the inadequate disposal of this waste, it was noticed the need to alternatives that allow the use of this material, since, currently, there is no recycling or use. The aim, therefore, was to verify that construction materials are an excellent matrix that receives this waste, providing a considerable reduction in its inadequate disposal and the possible environmental damage it generates. Specific mass analyzes, laser granulometry, thermogravimetry and differential thermal analysis, X-ray fluorescence, X-ray diffraction, scanning electron microscopy and infrared spectroscopy by Fourier transform were executed, using them to characterize the sludge. A value of 2.20 g/cm3 was obtained for its specific mass and an average diameter of 26.10 ± 0.65 μm, with 97.15% Regarding its composition, its main components are CaO, MgO and SiO2, the waste being a partially amorphous material of them having a diameter less than 80 μm, what characterized the textile sludge as a filler. Subjecting the sample to heating, it was evident that it has about 20% organic matter. The textile sludge presented positive evidence that reiterates your use in alternative building materials.